Alpha-Methylacyl-CoA Racemase (AMACR), a Potential New Biomarker for Glioblastoma - Lee, Hyunji; Kim, Minhee; Kim, Seon-Hwan; Tran, Quangdon; Kong, Gyeyeong; Kim, Chaeyeong; Kwon, So Hee; Park, Jisoo; Park, Jin Bong; Park, Sungjin; Park, Jongsun (Frontiers in Oncology, 2020)
Alpha-Methylacyl-CoA racemase (AMACR), which was initially discovered as a prostate cancer marker, is critical for the chiral inversion mechanism of branched-chain fatty acids. However, the function of AMACR in brain tumors has not been investigated. In this study, AMACR appeared to be involved in glioblastoma. The protein and mRNA levels of AMACR were highly elevated in glioblastoma. Downregulation of AMACR inhibited cell proliferation and migration. Comprehensive analysis of the public REMBRANDT GBM dataset also confirmed that the level of AMACR expression was correlated with the clinical prognosis of glioma patients. In summary, these findings indicate that AMACR expression is increased in a glioblastoma cell line and glioma patients, suggesting that AMACR might be a potential diagnostic marker and therapeutic molecule for cancer, including glioma.